The transferability and evolution of NDM-1 and KPC-2 co-producing Klebsiella pneumoniae from clinical settings - Gao, Hua (EBioMedicine, 2020)
BACKGROUND: Emergence of KPC-2 and NDM-1-coproducing carbapenem-resistant Klebsiella pneumoniae (KPC-2-NDM-1-CRKP) has escalated threat of CRKP to healthcare. Currently, only 4 isolates had been reported sporadically. It remains unclear how KPC-2-NDM-1-CRKPs emerged, and whether they are stable and have transmission capacity. METHODS: PCR and Sanger sequencing was used to screen carbapenemase genes for 2057 CRKP isolates, to identify KPC-2-NDM-1-CRKPs. The clinical information of the patients was collected from medical records. Antimicrobial susceptibility, plasmid stability, plasmid conjugation and growth curve were measured. The whole genomes were sequenced on PacBio and Illumina platforms. Similar plasmids were searched against public database. Phylogenetic tree was built based on related genomes which carried similar plasmids, to infer the evolutionary history of KPC-2-NDM-1-CRKP. FINDINGS: We identified to date the largest cohort of 7 KPC-2-NDM-1-CRKPs. An increased incidence rate was observed. Plasmid transferability assay and phylogenic analysis suggested an evolutionary pathway that KPC-2-NDM-1-CRKP emerged from a KPC-2-CRKP progenitor which acquired another highly transferable bla(NDM-1) plasmid later. Further, demographics and stability test revealed that these isolates were stable and had the potential for transmission among patients. INTERPRETATION: Our study extends our concern on KPC-2-NDM-1-CRKP about its high stability and non-inferior fitness, sheds light on the evolution of KPC-2-NDM-1-CRKP, strengthens the importance of continued surveillance on these isolates, and would improve clinical treatment and management. FUNDING: This work was supported by National Natural Science Foundation for Distinguished Young Scholars of China (81625014) and NSFC-RCUK-MRC (81661138006).